2018
DOI: 10.1002/pc.24757
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on the reinforcement mechanism of the nano‐sized carbonaceous filled epoxy‐glass fiber hybrid‐composites through analysis of fracture surfaces

Abstract: The objective of this work was to investigate the influence of delamination degree of the graphite on the mechanical properties of glass fiber/epoxy composite. To aim this, graphene and highly expanded graphite (HEG) nanofillers were synthesized using intensive ultrasonic method and were added to the epoxy and also glass fiber/epoxy composite, separately. Subsequently, tensile, flexural and impact strength of prepared samples were studied. Furthermore, the lateral size and dispersion quality of synthesized fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Thus, considering that the GNP platelets are well adhered to the matrix, crack propagation through the matrix is relatively difficult, and a higher surface interaction and more energy will be dissipated for fracture continuity. [ 64 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, considering that the GNP platelets are well adhered to the matrix, crack propagation through the matrix is relatively difficult, and a higher surface interaction and more energy will be dissipated for fracture continuity. [ 64 ]…”
Section: Resultsmentioning
confidence: 99%
“…They verified that, with the growth of the crack, the system with a weak platelet/matrix and platelet/platelet interface will present the GNP debonding mechanisms and also the GNP sheet delamination, respectively, [ 39,49 ] since delamination predominantly occurs in systems with agglomerates. [ 39,64,66 ]…”
Section: Resultsmentioning
confidence: 99%
“…In addition to block copolymers, carbon nanoparticles can be used to improve the mechanical properties of epoxy resins and, in particular, their toughness. [ 10–12 ] The nanoparticles used in this research (carbon nanotubes [CNTs], graphene, and carbon black) were chosen because they are the most studied nanoparticles in the literature [ 10–17 ] and they are mainly composed of carbon, only changing geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of nanoparticles into the polymer blends has been the subject of a great number of researches in academia and industry. This approach is associated with interesting results such as improving the mechanical properties, adding new characteristics, such as electrical properties, or controlling of the phase morphology . For example, Elias et al reported that silica nanoparticles induced a decrease in the effective interfacial tension between polypropylene (PP) and ethylene vinyl acetate phases and thereby a lower particle size for dispersed phase .…”
Section: Introductionmentioning
confidence: 99%
“…This approach is associated with interesting results such as improving the mechanical properties, adding new characteristics, such as electrical properties, or controlling of the phase morphology. [8][9][10][11][12][13][14] For example, Elias et al reported that silica nanoparticles induced a decrease in the effective interfacial tension between polypropylene (PP) and ethylene vinyl acetate phases and thereby a lower particle size for dispersed phase. [15] In another work, Palacios et al concluded that the fine-tuned morphology of the PP/polyamide-6 (PA-6) blends with enhanced ductility and barrier properties can be obtained at an optimum content of nanosilica and compatibilizer.…”
Section: Introductionmentioning
confidence: 99%